2021
DOI: 10.1111/irv.12880
|View full text |Cite
|
Sign up to set email alerts
|

Risk of symptomatic severe acute respiratory syndrome coronavirus 2 infection not associated with influenza vaccination in the 2019–2020 season

Abstract: The association of influenza vaccine and severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) infection was assessed by test-negative design using data collected for a study of outpatient COVID-19-like illness with onset dates from June to September 2020. Multivariable logistic regression models examined the association between receipt of 2019-2020 influenza vaccine and PCR-confirmed SARS-CoV-2 with adjustment for potential confounders. Receipt of influenza vaccine during the 2019-2020 influenza season… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 15 publications
0
8
0
Order By: Relevance
“…A total of 3,887 studies met the initial search criteria. After 3 rounds of screening, a total of 23 studies 3,5,15,[27][28][29][30][31][32][33][34][35][36][37][38][39][40][41][42][43][44][45][46] met the inclusion criteria. The detailed process of literature screening is shown in Figure 1.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…A total of 3,887 studies met the initial search criteria. After 3 rounds of screening, a total of 23 studies 3,5,15,[27][28][29][30][31][32][33][34][35][36][37][38][39][40][41][42][43][44][45][46] met the inclusion criteria. The detailed process of literature screening is shown in Figure 1.…”
Section: Resultsmentioning
confidence: 99%
“…In total, this study extracted unadjusted and adjusted RRs, HRs, or ORs from the original data for 23 studies for synthesis. Of these, 16 studies 3,[27][28][29][30][31][32][33][34][35][36][37][38][39][40][41] examined the association between influenza vaccination and the risk of COVID-19 infection, 7 studies 28,30,34,40,[42][43][44] examined the association between influenza vaccination and the risk of hospitalization in COVID-19 patients, 5 studies 15,34,[43][44][45] assessed the association between influenza vaccination and the risk of ICU admission in COVID-19 patients, and 6 studies 5,40,42,43,45,46 explored the association between influenza vaccination and the risk of death in COVID-19 patients. The results showed that influenza vaccination was associated with a reduced risk of COVID-19 infection (RR=0.83, 95% CI=0.76, 0.90, I 2 =80.8%).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Of the 92 full-text articles identified, 58 were excluded because they did not meet the inclusion criteria, and two others were obtained from the references. The remaining 36 articles reported on 55,996,841 subjects outcomes were included in this analysis [21–56] . None of the participants had received COVID-19 vaccination during the study period.…”
Section: Resultsmentioning
confidence: 99%
“…The following supporting information can be downloaded at: , Table S1. Baseline characteristics of the 21 publications, involving 22 studies that assessed the association between influenza vaccination and SARS-CoV-2 infection [ 15 , 29 , 31 , 32 , 33 , 36 , 37 , 38 , 40 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 60 ]. Table S2.…”
mentioning
confidence: 99%